Woman in a man's world - Campion, Nardi Reeder; Stanton, Rosamond Wilfley ([Boston?] : Little Brown, 1967)
This edition is for readers for whom English is a second language. It can be anyone whos has learned 1,000 words of english.
Original Title: Look to this day!Glossary.
Keywords: Novelas; Estados Unidos De America; Literatura Norteamericana